Study on tensile mechanical response and microstructure of polypropylene fiber reinforced loess under freezing - Yuxing Wang; Chunhui Liu; Yimin Zhong; Erqing Mao; Fei He (PLoS ONE, 2026)
Tensile strength is one of the key parameters in the mechanics of frozen ground, widely applied in the engineering design of frozen ground and theoretical research on frost heave. Fiber-reinforced soil technology has attracted considerable attention from numerous researchers. This study utilised a custom-designed tensile testing apparatus to investigate the influence of polypropylene fiber content, freezing temperature, and loading rate on the mechanical response of frozen loess. Combined with microscopic structural observations, the research elucidates the fiber reinforcement mechanism. Experiments revealed that fiber incorporation transformed the soil’s failure mode from brittle fracture to ductile failure, characterised by multiple fissures, significantly enhancing the material’s load-bearing capacity and deformation properties. Optimal reinforcement was achieved at a fiber content of 0.3%, with tensile strength increasing by 71.4% compared to unfibered soil. The stress-strain response exhibited sustained strengthening characteristics. Tensile strength exhibits exponential growth with decreasing freezing temperatures and linear increase with rising loading rates. The incorporation of fibers further enhances the material’s response capability under dynamic loading conditions. Microstructural analysis indicates that an appropriate fiber content effectively fills soil pores and forms a spatial network structure, whereas excessive fibers cause agglomeration due to uneven distribution, resulting in structural weakening. This research provides experimental evidence and theoretical reference for the design and application of fiber-modified frozen ground in engineering projects within cold regions